Aerophones in Flatland: Interactive Wave Simulation of Wind Instruments - Allen, Andrew; Raghuvanshi, Nikunj (ACM Transactions on Graphics (SIGGRAPH 2015), 2015)
We present the first real-time technique to synthesize full bandwidth sounds for 2D virtual wind instruments. A novel interactive wave solver is proposed that synthesizes audio at 128,000Hz on commodity graphics cards. Simulating the wave equation captures the resonant and radiative properties of the instrument body automatically. We show that a variety of existing non-linear excitation mechanisms such as reed or lips can be successfully coupled to the instrument’s 2D wave field. Virtual musical performances can be created by mapping user inputs to control geometric features of the instrument body, such as tone holes, and modifying parameters of the excitation model, such as blowing pressure. Field visualizations are also produced. Our technique promotes experimentation by providing instant audio-visual feedback from interactive virtual designs. To allow artifact-free audio despite dynamic geometric modification, we present a novel time-varying Perfectly Matched Layer formulation that yields smooth, natural-sounding transitions between notes. We find that visco-thermal wall losses are crucial for musical sound in 2D simulations and propose a practical approximation. Weak non-linearity at high amplitudes is incorporated to improve the sound quality of brass instruments. Presentation slides can be found here.